The Composition Effect of Bamboo Leaves and Goat Manure Fertilizer on Growth Mustard (Brassica juncea L.) - Harlina Kusuma Tuti Kusuma; Aditya Dyah Utami (SEAS (Sustainable Environment Agricultural Science), 2023)
The mustard plant is a commercially valuable vegetable popular with the public, so demand for this vegetable continues to increase. One of the factors that influences growth in terms of external factors is the planting medium. Planting media made from organic materials is a solution to using chemicals that cause residues that damage the environment. This research was conducted to determine the best type of planting media and the composition of the planting media for the growth of kale plants. Treatment using P1 (Control) = soil; P2 = soil: organic fertilizer (goat manure) (1:1); P3 = soil: bamboo leaves (1:1) using Randomized Complete Block Design method with five replications. The research results on planting media treatment with goat manure influenced the growth of mustard greens, including plant height, number of leaves, leaf length, root length, and root wet weight.